Electron Microscope Observation of Acupuncture and Nerve Repair in the Treatment of Peripheral Facial Paralysis - Zhenggen Shan (Emergency Medicine International)
The repair of peripheral facial paralysis is a long-term problem in neurosurgery, and nerve repair is often needed. Due to the high differentiation of nerve tissue and the slow regeneration of peripheral nerve fibers, the repair effect after peripheral nerve injury is not ideal. In recent years, studies have found that the inflammatory response after peripheral nerve injury also has an important impact on the repair of peripheral nerve defects. This study depends on the utilization of traditional needle therapy in the treatment of fringe facial loss of motion, and the clinical adequacy of needle therapy in addition to nerve fix in the intense period of fringe facial loss of motion was seen with an electron magnifying lens. Endeavor to give significant exploration results to the clinical treatment of fringe facial loss of motion gives a straightforward, simple, protected, and successful new treatment innovation for the clinical treatment of the infection and enriches the treatment plan for peripheral facial paralysis. Transmission electron microscopy observations showed that 21 days after the artificial nerve was repaired, the nerve injury showed different degrees of recovery, and the myelin sheath was forming and gradually wrapping the new axons, which was similar to the catheter group (NC) and hydrogel group (HC). In contrast, the myelin layer of the fibroblast group (FHC) is more obvious, and the repair effect is better. In the maintenance of fringe nerve surrenders, irritation is an unavoidable interaction, and moderate needle therapy is useful to advance the maintenance of fringe nerve abandons. Talking about the law of nerve fix reaction in fringe nerve imperfection fix is helpful to the examination of fringe nerve deformity fix. Tests have shown that utilizing needle therapy and moxibustion joined with nerve fixes has accomplished great outcomes in the treatment of fringe facial loss of motion, and the patient’s recuperation rate has expanded by over 30%.